Integration of specialized application software for multimedia projects / Siti ‘Aisyah Sa’dan, Dr. Nooradilla Abu Hasan and Ts. Dr. Rashidah Mokhtar - Sa’dan, Siti ‘Aisyah; Abu Hasan, Nooradilla; Mokhtar, Rashidah (Academy of Language Studies, Universiti Teknologi MARA Negeri Sembilan Branch, Rembau Campus, 2025)
Specialized Application Software for Multimedia Projects refers to software tools designed specifically for creating, editing, and managing multimedia content, such as videos, images, animations, and audio. These applications provide advanced features tailored for professionals and enthusiasts in fields like graphic design, video production, game development, and web design. The software can be categorized into multimedia software, graphic design tools, web authoring programs, gaming design software, artificial intelligence applications, and virtual reality platforms.